(untitled) (REMUNOM, 2024)
This study aims to carry out a critical analysis of the effectiveness of the socio-educational measures established by the Statute of the Child and Adolescent (ECA). To this end, the paper takes a historical look at the development and consolidation of the Statute up to its current position in Brazilian legislation. Based on a detailed analysis of the practical application of socio-educational measures, the study investigates their definitions, characteristics, advantages and disadvantages, as well as evaluating the rights of children and adolescents subjected to these measures. The main focus is to answer whether these measures, in their current form, are effective or whether they need to be supplemented in order to fully fulfill their purpose. The conclusion of the study indicates that there is a need to improve the measures so that they can achieve their objectives without harming juvenile offenders.